Sustainable Fashion and Social Media: Inditex´s Strategy to Justify Premium Prices - Reinoso-Barbero, Laura; de Garcillán López-Rua, Mencía; Ruiz-Campo, Sofía (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The article analyzes the communication of Corporate Social Responsibility (CSR) in the fashion sector, with special focus on Inditex. The relationship between sustainability, consumer perception and communication strategy is examined, highlighting the role of social networks in the legitimization of business practices. Through an empirical study based on surveys and content analysis on networks, deficiencies in the visibility and effectiveness of Inditex's sustainable message are identified. The findings highlight the need to improve transparency and communication segmentation to strengthen consumer trust and their willingness to pay more for sustainable products.